2017
DOI: 10.1038/bjc.2017.190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum microRNA biomarkers for gastric cancer based on blood and tissue pools profiling: the importance of miR-21 and miR-331

Abstract: Background:High stability and disease-specific disarrangements suggest that microRNA molecules (miRNAs) present in body fluids are ideally suited for diagnostic applications, including gastric cancer (GC). However, the actual source of circulating miRNA biomarkers in GC has not been adequately evaluated, particularly in the Western populations that have some distinct characteristics compared with Asian patients.Methods:Twenty treatment-naive patients with GC along with 20 cancer-free controls were recruited. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 38 publications
3
64
0
Order By: Relevance
“…D a, b) The analysis of miR-192-5p expression shown that the level of miR-192-5p was not significantly reduced, neither in colon cancer tissues nor serum samples when compared with normal counterparts seems, the evaluation of miR-9-5p in serum of patients, suffering from gastric cancer, can be considered as a biomarker. This result was similar to some studies which monitored different microRNAs in serum samples [29,30]. The stimulatory of miR-9 in cancer progression is not only restricted to gastric cancer, since other studies also suggested that the expression of this miRNA could be altered in other human malignancies, including squamous cell carcinoma [31], breast cancer [32] and non-small-cell lung cancer [33].…”
Section: Discussionsupporting
confidence: 89%
“…D a, b) The analysis of miR-192-5p expression shown that the level of miR-192-5p was not significantly reduced, neither in colon cancer tissues nor serum samples when compared with normal counterparts seems, the evaluation of miR-9-5p in serum of patients, suffering from gastric cancer, can be considered as a biomarker. This result was similar to some studies which monitored different microRNAs in serum samples [29,30]. The stimulatory of miR-9 in cancer progression is not only restricted to gastric cancer, since other studies also suggested that the expression of this miRNA could be altered in other human malignancies, including squamous cell carcinoma [31], breast cancer [32] and non-small-cell lung cancer [33].…”
Section: Discussionsupporting
confidence: 89%
“…Many miRNAs are known to be involved in oncogenesis, tumor progression, and metastasis by targeting tumor suppressors, oncogenes, or other proteins associated with disease progression or drug resistance [4][5][6][7][8]. Differential expression of miRNAs in biological fluids of patients with different cancers and healthy donors has been previously reported by many groups [7,[9][10][11][12][13][14][15]. Other reports also showed extracellular vesicles (EVs) and cell-free nucleoprotein complexes carry distinct populations of miRNA, and the content of these miRNA pools can be used to develop promising tools for PCa screening [16,17].…”
Section: Introductionmentioning
confidence: 91%
“…Many cell-free miRNAs showed altered expression patterns in different types of cancers instead of a certain type, and also similar expression between benign and malignant tumors; miR-21-5p, miR-155-5p and miR-210-3p for example, are all involved in many cancer types, but for miR-21-5p, significantly increased levels in plasma of CRC patients were observed, but it could not distinguish between malignant cancer and benign polyps [309]. In patients with NSCLC [175,[310][311][312][313], liver cancer [314] or gastric cancer [315,316], it was reportedly upregulated, but the same molecule was downregulated in patients suffering from breast cancer [188,313]. This means that the contribution of miRNAs in various types of cancers differs.…”
Section: Why Are Mirnas Not Used In Current Practice?mentioning
confidence: 99%